Pentingnya Pendidikan Karakter bagi Siswa SMA di Era Digitalisasi di Kecamatan Nusalaut Kabupaten Maluku Tengah - Salong, Amjad; Pattiasina, Johan; Latuserimala, Gerald; Dulhasyim, Ashari; Kermite, Joicelina (Universitas Pattimura, 2024)
In the digital era, character education has become essential for shaping the personality of young individuals to be ethical and responsible. This study aims to explore the importance of character education in high schools in Nusalaut District, Central Maluku Regency. The findings indicate that digitalization significantly influences how students access information, interact, and develop their character. Without adequate control, the use of technology can negatively impact students' empathy and social skills. Therefore, integrating character education into the school curriculum through value-based approaches and programs like extracurricular activities is crucial. The involvement of teachers, parents, and the community is necessary to ensure that students can utilize technology wisely. With strong character education, students are expected to adapt to the challenges of the digital era while upholding moral values